2021
DOI: 10.1002/pts.2601
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of changes in torsional stiffness of press‐formed paperboard packages induced by heat load utilizing a developed measuring device

Abstract: The press-forming process and the effects of parameter variation on the forming process have attracted great interest lately. The dimensional accuracy of the formed trays and the rigidity and stability of the packages are crucial factors for functionality in packaging lines, especially in fast operating machinery. The torsional stiffness of trays must be at a sufficient level to ensure the functionality in subsequent processes and logistics. The objective of this study was to develop and build a device for mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…Numerous materials are being actively tested for comprehensive prediction of coated substrate behaviour during converting operations (Girlanda and Fellers 2007). As paperboard possess viscoelastic nature with time-dependent creep (Tanninen et al 2021a) and a tendency to show spring back and walls deflection after forming (Hauptmann et al 2011), materials with higher stiffness and lower recoverable strain component tend to have better formability (Vishtal et al 2014). In this regard, to produce trays with higher stiffness, it is recommended to cut blanks along the MD, meaning that the ready tray's longer side will be parallel to the machine direction.…”
Section: Mechanical Propertiesmentioning
confidence: 99%
See 3 more Smart Citations
“…Numerous materials are being actively tested for comprehensive prediction of coated substrate behaviour during converting operations (Girlanda and Fellers 2007). As paperboard possess viscoelastic nature with time-dependent creep (Tanninen et al 2021a) and a tendency to show spring back and walls deflection after forming (Hauptmann et al 2011), materials with higher stiffness and lower recoverable strain component tend to have better formability (Vishtal et al 2014). In this regard, to produce trays with higher stiffness, it is recommended to cut blanks along the MD, meaning that the ready tray's longer side will be parallel to the machine direction.…”
Section: Mechanical Propertiesmentioning
confidence: 99%
“…In this regard, to produce trays with higher stiffness, it is recommended to cut blanks along the MD, meaning that the ready tray's longer side will be parallel to the machine direction. In addition, it has been found that coated trays demonstrate significantly higher stiffness than non-coated ones due to greater thickness (Tanninen et al 2021a). Initially, it may seem that the convertibility of a material is determined by its substrate, which is much thicker than the coating.…”
Section: Mechanical Propertiesmentioning
confidence: 99%
See 2 more Smart Citations
“…5 Furthermore, a device was developed for measuring the torsional stiffness of various MPPs. 6 Another critical research trend is investigating the material behavior of molded pulp. The tensile and compressive elastic modulus of molded pulp were measured as 225 and 130 N/mm 2 , respectively.…”
Section: Introductionmentioning
confidence: 99%